2012
DOI: 10.1189/jlb.0212100
|View full text |Cite
|
Sign up to set email alerts
|

The immune theory of psychiatric diseases: a key role for activated microglia and circulating monocytes

Abstract: This review describes a key role for mononuclear phagocytes in the pathogenesis of major psychiatric disorders. There is accumulating evidence for activation of microglia (histopathology and PET scans) and circulating monocytes (enhanced gene expression of immune genes, an overproduction of monocyte/macrophage-related cytokines) in patients with bipolar disorder, major depressive disorder, and schizophrenia. These data are strengthened by observations in animal models, such as the MIA models, the chronic stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
194
0
5

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 306 publications
(211 citation statements)
references
References 229 publications
10
194
0
5
Order By: Relevance
“…A combination of genetic and environmental factors resulting in some immune dysregulation in general and the lack of the CMV IgG antibodies in particular could be the most plausible speculations. While there are no specific research results supporting this finding in existing literature, the activation of the immune system and prolonged neuroinflammation are well established phenomena implicated in the etiopathogenesis and symptomatology of schizophrenia (Lin et al, 1998;Nikkila et al, 1999;Kim et al, 2000;Theodoropoulou et al, 2001;Ebrinc et al, 2002;Patterson, 2002;Zhang et al, 2002;Garver et al, 2003;Zhang et al, 2004;Coelho et al, 2008;Potvin et al, 2008;Doorduin et al, 2009;Kim et al, 2009;Song et al, 2009;Drexhage et al, 2010;Romero et al, 2010;Drexhage et al, 2011;Weigelt et al, 2011;Beumer et al, 2012;Brito-Melo et al, 2012). Other mechanisms could also be considered.…”
Section: Discussionmentioning
confidence: 56%
“…A combination of genetic and environmental factors resulting in some immune dysregulation in general and the lack of the CMV IgG antibodies in particular could be the most plausible speculations. While there are no specific research results supporting this finding in existing literature, the activation of the immune system and prolonged neuroinflammation are well established phenomena implicated in the etiopathogenesis and symptomatology of schizophrenia (Lin et al, 1998;Nikkila et al, 1999;Kim et al, 2000;Theodoropoulou et al, 2001;Ebrinc et al, 2002;Patterson, 2002;Zhang et al, 2002;Garver et al, 2003;Zhang et al, 2004;Coelho et al, 2008;Potvin et al, 2008;Doorduin et al, 2009;Kim et al, 2009;Song et al, 2009;Drexhage et al, 2010;Romero et al, 2010;Drexhage et al, 2011;Weigelt et al, 2011;Beumer et al, 2012;Brito-Melo et al, 2012). Other mechanisms could also be considered.…”
Section: Discussionmentioning
confidence: 56%
“…Growing evidence indicates that the immune system is involved in the pathogenesis of psychotic disorders, including schizophrenia and bipolar disorder (67). CB2 mRNA levels were decreased in peripheral blood mononuclear cells of schizophrenia patients after treatment with olanzapine (186).…”
Section: Schizophreniamentioning
confidence: 99%
“…1 In schizophrenia, there is also accumulating evidence for a role of immune signaling. 2 For example, an increased peripheral concentration of IL-1 receptor antagonist (IL-1Ra) has been reported in patients with schizophrenia, 3 and knockout mice lacking IL-1Ra develop spontaneous joint inflammation. 4 Recent genome-wide association studies of schizophrenia have also found strong associations with markers spanning the MHC region, 5 indicating a possible role for adaptive immunity also in schizophrenia.…”
Section: Introductionmentioning
confidence: 99%